Instructor Perception of Incorporating Active Learning in College of Agriculture Classrooms - Karcher, Elizabeth; Guberman, Daniel; Bonem, Emily; Lumkes, John (Teaching and Learning Inquiry, 2022)
Significant numbers of studies declare the effectiveness of “active learning” and numerous universities develop programs to support the incorporation of active learning methods, yet despite various incentives, adoption is met with resistance. This work shares the results of a study of instructor perceptions about active learning at a large research university in the United States. Instructor motivation, perceptions of competence and autonomy (related to colleagues and administrators), experience in training programs, as well as actual practices were explored with regard to active learning. Drawing on self-determination theory, this exploratory study will help universities in developing strategies for increasing the adoption of evidence-based teaching practices. Our results suggest that the work climate related to colleagues, gender, and participation in a Faculty Learning Community influenced both the implementation and motivation to implement active learning in the classroom.